Gut microbiome alterations in Alzheimer's disease. Issue 1 (December 2017) - Vogt, Nicholas; Kerby, Robert; Dill-McFarland, Kimberly; Harding, Sandra; Merluzzi, Andrew; Johnson, Sterling; Carlsson, Cynthia; Asthana, Sanjay; Zetterberg, Henrik; Blennow, Kaj; Bendlin, Barbara; Rey, Federico
Abstract Alzheimer's disease (AD) is the most common form of dementia. However, the etiopathogenesis of this devastating disease is not fully understood. Recent studies in rodents suggest that alterations in the gut microbiome may contribute to amyloid deposition, yet the microbial communities associated with AD have not been characterized in humans. Towards this end, we characterized the bacterial taxonomic composition of fecal samples from participants with and without a diagnosis of dementia due to AD. Our analyses revealed that the gut microbiome of AD participants has decreased microbial diversity and is compositionally distinct from control age- and sex-matched individuals. We identified phylum- through genus-wide differences in bacterial abundance including decreased Firmicutes, increased Bacteroidetes, and decreasedBifidobacterium in the microbiome of AD participants. Furthermore, we observed correlations between levels of differentially abundant genera and cerebrospinal fluid (CSF) biomarkers of AD. These findings add AD to the growing list of diseases associated with gut microbial alterations, as well as suggest that gut bacterial communities may be a target for therapeutic intervention.